The white queen - Gregory, Philippa (New York, N.Y. : Touchstone, 2009)
A tale of the Wars of the Roses follows Elizabeth Woodville, who ascends to royalty and fights for the well- being of her family, including two sons whose imprisonment in the Tower of London precedes a devastating unsolved mystery.
Includes bibliography, p. 413-415.
Keywords: Elizabeth, -- Consort of Edward IV, King of England, -- 1437?- 1492 -- Fiction; Edward -- V, -- King of England, -- 1470-1483 -- Fiction; Richard, -- Duke of York, -- 1472-1483 -- Fiction; Richard -- III, -- King of England, -- 1452-1485 -- Fiction; Queens -- Great Britain -- Fiction; Great Britain -- History -- Edward IV, 1461-1483 -- Fiction; Great Britain -- History -- Richard III, 1483-1485 -- Fiction; Great Britain -- History -- Wars of the Roses, 1455-1485 -- Fiction; Biographical fiction; Historical fiction